Different Neurologic Aspects of Nutritional B12 Deficiency in Infancy. (April 2016) - Yilmaz, Sanem; Serdaroglu, Gul; Tekgul, Hasan; Gokben, Sarenur
The objective of this study is to evaluate neurologic problems caused by nutritional vitamin B12 deficiency in infancy. Twenty-four cases between 2 and 18 months of age with neurologic symptoms and/or signs and diagnosed as nutritional vitamin B12 deficiency were analyzed. The most common symptoms were developmental retardation, afebrile seizures, and involuntary movements. The mean vitamin B12 levels were lower in patients with both neurologic and extraneurologic involvement when compared to those with only neurologic symptoms. All of the cases were treated with vitamin B12 . In patients with severe deficiencies, involuntary movements were observed during vitamin B12 treatment using cyanocobalamin form. At the 1-year follow-up, all but 3 patients were considered neurodevelopmentally normal. The 3 patients that did not fully recover, on admission, had the lowest vitamin B12 levels. It is of great importance to prevent, diagnose, and treat vitamin B12 deficiency promptly to prevent the long-term neurologic problems.